Protecting Privacy on Social Media: Mitigating Cyberbullying and Data Heist Through Regulated Use and Detox, with a Mediating Role of Privacy Safety Motivations - Jing Niu; Bilal Mazhar; Inam Ul Haq; Fatima Maqsood (Social Media + Society)
Information theft and cyberbullying pose significant threats to users’ privacy on social media. This study applies Protection Motivation Theory (PMT) to explore how online information disclosure awareness and privacy concerns influence protective actions, such as regulated social media usage and detoxification, in response to negative experiences like data heist and cyberbullying. Analyzing survey responses from 1,000 social media users in Pakistan, ranging in age from 18 years to over 50, and using the snowball sampling technique, our findings reveal that awareness of online information disclosure mediates the relationship between data theft and regulated social media use. Privacy concerns similarly mediate the relationship between cyberbullying experiences and social media detoxification, aligning with PMT. In addition, negative online experiences directly correlate with privacy safety behaviors, indicating that motivations may not always drive protective actions. This research sheds light on the intricate dynamics between privacy concerns, negative online experiences, and protective behaviors, offering insights for interventions and policies to enhance users’ digital privacy and safety. Understanding these relationships is crucial for addressing the challenges of information theft and cyberbullying in the digital landscape.